2004
DOI: 10.1364/ao.43.002125
|View full text |Cite
|
Sign up to set email alerts
|

Silica-nanoparticle-dispersed methacrylate photopolymers with net diffraction efficiency near 100%

Abstract: We demonstrate volume holographic recording in silica-nanoparticle-dispersed methacrylate photopolymers with reduced scattering loss as low as 2%. This is made possible by use of 13-nm silica nanoparticles. As a result a net diffraction efficiency near 100% is achieved for a transmission volume hologram of 45-microm thickness. Grating buildup dynamics are measured for various nanoparticle concentrations, and the effects of nanoparticle size on refractive-index modulation and polymerization shrinkage are also e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
99
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(108 citation statements)
references
References 12 publications
6
99
1
Order By: Relevance
“…It has been previously shown [12][13][14][15][16][17][18][19][20][21][22] that the holographic recording process in nanoparticle doped photopolymerisable materials can lead to the redistribution of the nanoparticles and thus to the creation of patterns of particle rich and particle depleted areas ( Figure 1B). The diffraction efficiency, η, of such a volume phase hologram is given by (2):…”
Section: Theorymentioning
confidence: 89%
See 1 more Smart Citation
“…It has been previously shown [12][13][14][15][16][17][18][19][20][21][22] that the holographic recording process in nanoparticle doped photopolymerisable materials can lead to the redistribution of the nanoparticles and thus to the creation of patterns of particle rich and particle depleted areas ( Figure 1B). The diffraction efficiency, η, of such a volume phase hologram is given by (2):…”
Section: Theorymentioning
confidence: 89%
“…The basic idea behind the concept of the photopolymerizable nanocomposites is to introduce nano-dopants with significantly different refractive index from that of the host material and to achieve redistribution of the nano-dopants during holographic recording. [12][13][14][15][16][17] It has been shown that optimum values of recording intensity and volume fractions of incorporated solid nanoparticles such as SiO 2 18 , TiO 2 19 and ZrO 2 20 , lead to an increase of diffraction efficiency of the recorded gratings due to a higher refractive index modulation.…”
Section: Introductionmentioning
confidence: 99%
“…Inorganic nanoparticles embedded in a photopolymer matrix (nanoparticle-polymer composites) have already been investigated intensively [12][13][14] for light-optics applications. In nanoparticle-polymer gratings, the refractive-index modulation amplitude Dn for neutrons can be tuned by choosing a suitable value of b c , i.e., the species of nanoparticles.…”
mentioning
confidence: 99%
“…For instance, 13 nm silica nanoparticles were added to the methacrylate photopolymers by Suzuki et al, and a noticeable reduction of scattering loss and a high-contrast refractive-index change were achieved [59]. A gold-nanoparticle-doped photopolymer was used to suppress side lobes of angle selectivity of volume holographic gratings by Cao et al, achieving a higher diffraction efficiency [60,61].…”
Section: Diffraction Efficiencymentioning
confidence: 99%